The handbook of pragmatics - Horn, Lawrence; Ward, Gregory (Blackwell handbooks in linguistics., 2007)
This collection of articles outlines the central themes and challenges for current research in the field of linguistic pragmatics. The 33 articles provide an authoritative and accessible introduction to the field.